Case Report: A Case of β-Ureidopropionase Deficiency Complicated With MELAS Syndrome Caused by UPB1 Variant and Mitochondrial Gene Variant - Shu, Jianbo; Zhi, Xiufang; Chen, Jing; Lei, Meifang; Zheng, Jie; Sheng, Wenchao; Zhang, Chunhua; Li, Dong; Cai, Chunquan (Frontiers in Pediatrics, 2022)
Background: β-ureidopropionase deficiency is a rare autosomal recessive disease affecting the last step of pyrimidine degradation and Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes syndrome is a rare inherited disorder caused by genetic defects in mitochondrial DNA. Case presentation: A 8-year-old boy presented with dizziness, vomiting and convulsions. The gas chromatography-mass spectrometry showed β-ureidopropionase deficiency. Analysis of whole exome sequencing detected homozygous missense variant c.977G>A (p.R326Q) in UPB1. But the patient had persistent hyperlactacidemia and metabolic acidosis, which was not consistent with the classic features of β-ureidopropionase deficiency, combined with the manifestations of developmental delay, poor academic performance and poor sports stamina, so the mitochondrial DNA genetic analysis was performed. The results indicated the mutation m.3243A>G of MT-TL1 gene. The heteroplasmy level was 65% and that of patient’s mother was 17.8%. Eventually, the ultimate diagnosis of β-ureidopropionase deficiency combined with MELAS syndrome was established. Conclusions: The report about β-ureidopropionase deficiency caused by nuclear gene variation and MELAS syndrome caused by mitochondrial gene variant coexisting in the same patient enriches the clinical study of these two rare diseases.